2023
DOI: 10.1007/s10340-023-01593-w
|View full text |Cite
|
Sign up to set email alerts
|

Expanding risk predictions of pesticide resistance evolution in arthropod pests with a proxy for selection pressure

Abstract: Chemical resistance in pest organisms threatens global food security and human health, yet resistance issues are mostly dealt with reactively. Predictive models of resistance risk provide an avenue for field practitioners to implement proactive pest management but require knowledge of factors that drive resistance evolution. Despite the importance of chemical selection pressure on resistance evolution, poor availability of chemical usage data has limited the use of a general multi-species measure of selection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…This is compounded by the low level of authorized chemical molecules in Colombia. The lack of variety in treatments contributes to increased selection pressure (Thia et al, 2023), resulting in high levels of pyrethroid resistance, as reported by Daglish & Nayak (2018) in eastern Australia. This phenomenon has been noted in other stored grain pests (Attia et al, 2020;Haddi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This is compounded by the low level of authorized chemical molecules in Colombia. The lack of variety in treatments contributes to increased selection pressure (Thia et al, 2023), resulting in high levels of pyrethroid resistance, as reported by Daglish & Nayak (2018) in eastern Australia. This phenomenon has been noted in other stored grain pests (Attia et al, 2020;Haddi et al, 2018).…”
Section: Resultsmentioning
confidence: 99%